Women's voices of anger frustration and despair : (Womyn's Agenda for Change (WAC), 2003)
These stories show the impact of such policies on poor Cambodian women. Each story is real (though their names have changed to protect their identities). Each story demonstrates how gender discrimination merges and entwines itself with trade liberalization policies to generate more inequity for women, more despair and more violence.